A Formative Qualitative Study on the Acceptability of Deferred Consent in Adult Emergency Care Research in Malawi. (October 2019) - Manda-Taylor, Lucinda; Bickton, Fanuel Meckson; Gooding, Kate; Rylance, Jamie
Research in emergency medical care is challenging due to a limited therapeutic window for intervention, which may compromise informed consent. "Deferred consent" allows initiation of study procedures before full consent is recorded. We conducted a formative qualitative study exploring perspectives on deferred consent in Malawi among research ethics committee members, health care professionals, and lay representatives. Participants identified several advantages of deferred consent including scientific value and potential health benefits to the study subjects and wider population. Participants also had concerns, including regulatory barriers and the risk of abuse and malpractice. Conditions affecting acceptability are related to the role of proxies, the nature of the research, the availability of robust regulatory oversight, and the need for community engagement. Our findings show deferred consent would be acceptable in Malawi, provided that a clear case can be made to advance medical knowledge and that adequate regulatory and ethical protections are in place.